Makna Komunikasi Shopkeeper Bagi Konsumen dalam Proses Belanja di Domayn Store - Aritonang, Wendy Ricardho; Khairullah, Khairullah (Universitas Medan Area, 2025)
This study aims to understand the meaning of communication between shopkeepers and consumers in the shopping process at Domayn Store. Using a descriptive qualitative approach, it focuses on how consumers interpret their communication experiences and how these interactions influence comfort, trust, and purchasing decisions. Data were collected through in-depth interviews with consumers and shopkeepers, as well as direct observation in the store. The findings reveal that communication characterized by friendliness, empathy, and clarity of information is understood by consumers not merely as service, but also as a form of appreciation. Friendliness is perceived as attentiveness, empathy fosters emotional closeness, and clear product information builds consumer trust in decision-making. Thus, interpersonal communication by shopkeepers carries meaning beyond simple transactions. It creates harmonious relationships, enhances comfort, and strengthens consumer loyalty to Domayn Store. These findings highlight the importance of meaningful communication in shaping positive shopping experiences in contemporary retail.